Step-wise approach to developing a scale-independent design space for functional tablet coating process. (2nd April 2020) - Debevec, Veronika; Stanić Ljubin, Tijana; Jeraj, Žiga; Rozman Peterka, Tanja; Bratuž, Borut; Gašperlin, Dušan; Srčič, Stanko; Horvat, Matej
Abstract: The objective of this study is to present a practical example of a scale-independent design space development using a step-wise approach. A detailed description of the development process with a systematic outline of the main steps is provided. Design space is developed for film coating of tablets with moisture protective polyvinyl alcohol (PVA) based coating. The impact of scale-independent coating process parameters on the properties of film-coated tablets (FCT), i.e. water activity and film coating protection ability, and consequently on product long-term stability is explored. The main finding is that with model simplifications, a step-wise approach and rational development of scale-independent design space for the coating process, it is possible to efficiently predict, control, and optimize the long-term stability of a moisture sensitive product. However, the PVA moisture protective coating itself is recognized as having conflicting effects on product stability.